Tests of the physical condition of elite swimmers: A manual for coaches - Rushall, B. S. (Sports Science Associates, 1995)
This text describes a rationale that supports the use of "field" tests, as opposed to "laboratory/physiological" tests, for determining the training progress of elite swimmers. Each evaluation procedures is laid out in a step-by-step format. Master copies of all recording and computation sheets are provided. Tests for the following are described. - Swimming power and/or propelling efficiency. - Strength training effectiveness. - Sprinting adaptation. - Endurance adaptation. - Training effects. - Estimation of anaerobic threshold training intensities and state. - Estimation of maximum aerobic capacity training intensities and state. - Estimation of lactate tolerance training intensities and state.